Design intelligent maximum power point tracking for photovoltaic at Universitas Airlangga - Herlambang Setiadi; Firdaus Bima Firmansyah; Prisma Megantoro; Tahta Amrillah; Herri Trilaksana; Galih Bangga; Muhammad Abdillah; Awan Uji Krismanto (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Rooftop photovoltaic (PV) plant is one ot the independent electricity that us favorable in recent year. Rooftop PV plant can be used as the source of smart building as well as fast charging station. Although rooftop PV plant could provide clean and sustainable energy from solar, they also come with disadvantages in term of intermittent power output. This intermittent power output is due to the uncertainty of the source. To tackle this problem, maximum power point tracking method is essential. Maximum power point tracking (MPPT) method can be used to extract maximum power from the solar cell in all conditions. This paper proposes an intelligent method for designing DC-DC MPPT based on fruit fly optimization (FFO) on realistic rooftop PV plant. Practical rooftop PV plant in Universitas Airlangga is employed as the testing system. The proposed method's efficacy is evaluated using time domain simulation. According to the simulation results, the proposed method can significantly extract power from PV.